Os EUA em cena : liberdade como construto no teatro político de Tony Kushner - Nogueira, Vanessa Cianconi Vianna (2013)
The aim of this dissertation is to examine how the idea of freedom, imbedded in the US imaginary, is represented in three of Tony Kushner s plays. The plays to be analyzed are: A Bright Room Called Day, Hydriotaphia or the Death of Dr. Browne: an Epic Farse about Death and Primitive Capital Accumulation and parts I and II of Angels in America (Millennium Approaches and Perestroika). A Bright Room describes the relationship between past and present and the fact that this connection can no longer be ignored in today s world. The warning given by Kushner is linked to what freedom and its link to happiness means to Americans. In order to do so, Kushner uses the figure of a ghost, Die Alte, who points to a direction that is opposite to that which ghosts that appear in drama usually take, in that the specter points to an impossible and barbaric future in which it is not possible to be hopeful anymore. Hydriotaphia or the Death of Dr. Browne: an Epic Farse about Death and Primitive Capital Accumulation, set in the 17th century, is a critique of the capitalist system of never-‐ending accumulation. Karl Marx s Communist Manifesto and its maxim everything that is solid melts into air pervades the entire play. In Angels in America, I seek to argue that the masks of North American tragedy, discussed by Dan Vogel, are personified in Roy Cohn, in Harper, and in the angel, respectively. The playwright who affirms he does not believe in the possibility of hope anymore (either to be free or to be happy), paradoxically, writes plays in which there is always a light at the end of the tunnel, a moment in which everything can be changed.